Ethics in sport - Morgan, William John 1948-; Meier, Klaus V. 1945-; Schneider, Angela Jo-Anne 1959- (Human Kinetics, 2001)
This text examines key issues such as drugs in sport, violence, scandals and unethical practices. A comprehensive coverage of the ethical issues confronting sport in contemporary society.